Sustainable automated and connected transport - Thomopoulos, Nikolas; Attard, Maria; Shiftan, Yoram (Transport and sustainability ;, 2024)
The UN Sustainable Development Goals (SDGs) are increasingly a core objective for policy makers, practitioners and citizens. Transport continues to be a core focus of these policy objectives, with Automated and Connected Transport (ACT) featuring as a potential solution to relevant challenges. Yet, there is still a lot to be achieved aside technological advancements. Sustainable Automated and Connected Transport highlights existing gaps and offers evidence-based recommendations for practitioners and policy makers to aid in meeting sustainability goals. Contributions link documented challenges of Autonomous and Connected Transport with sustainability. Based not only on activities of the international WISE-ACT network, but also on input by external experts, findings of contemporary and ongoing research are summarised to offer evidence-based sustainability recommendations. Sustainable Automated and Connected Transport addresses all three sustainability pillars, namely social, environmental and economic, within a single volume. Overall, Sustainable Automated and Connected Transport is a valuable source of ACT information for academics, practitioners and policy makers. Such a unified overview is beneficial to developing holistic research methods and global policies for making progress towards the SDGs. The Transport and Sustainability series addresses the important nexus between transport and sustainability, containing volumes dealing with a wide range of issues relating to transport, its impact in economic, social and environmental spheres and its interaction with other policy sectors.